Proceso de Atención de Enfermería en Recién Nacido a Termino con insuficiencia Respiratoria Aguda. - Muñoz Martinez, Lexsoy Vanessa (2022)
The present clinical case was based on the process of nursing care in a newborn at the end of 37,5 weeks of gestation with a clinical diagnosis of acute respiratory failure, which is a condition characterized by the accumulation of liquid in the air sacs in the lungs that do not allow oxygen to reach the organs. Therefore, it is intended to determine the causes of the problem in the newborn and carry out the appropriate nursing interventions in order to contribute to the relief of the patient´s signs and symptoms and improve their health status. The methodology used was based on the investigation of the causes, clinical picture, treatment and diagnosis of the pathology. Taking into account the clinical status of the patient, the physical assessment, and based on the dysfunctional patterns, the PAE (nursing care process) was prepared. A nursing plan was planned according to the most characteristic needs of the newborn in order to identify if the nursing interventions carried out helped in the prompt recovery of the patient. With this clinical case we can conclude that as long as a correct nursing care plan is carried out, the improvement of the clinical picture and recovery are achieved thanks to medical treatment and nursing interventions.